(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Since December 2019, the COVID-19 virus has been creating havoc and has spread to almost every corner of the world. The ongoing condition has several repercussions like deterioration in public mental health and rise in suicide cases. Amidst all the negativities, there is some good news. There have been fewer deaths due to The aim of our study was to study the pattern of deaths A total of 809 cases in 2019 and 553 cases in 2020 MKCG Medical college and hospital, Berhampur, Odisha, India